The effect of cognitive avoidance on rumination in college students: the chain mediating role of perfectionism and stress - An, Debao; Wang, Jiale; Xia, Yeling; Xing, Wenlong (Frontiers in Psychology, 2025)
This study aimed to examine the effect of cognitive avoidance on rumination among college students, and to explore the mediating roles of perfectionism and stress. Cognitive avoidance involves efforts to evade distressing thoughts, while rumination refers to repetitive negative thinking. A cross-sectional survey was conducted via convenience sampling among students from four universities in Xinjiang, Henan, and Guangdong. A total of 6,000 electronic questionnaires were distributed, and 5,412 valid responses were retained (effective rate: 90.20%). Participants completed the Cognitive Avoidance Questionnaire, Rumination Scale, Positive and Negative Perfectionism Scale, and the Depression Anxiety and Stress Scale (DASS-21). Pearson correlations and mediation analyses using PROCESS were performed. Results showed that cognitive avoidance, perfectionism, stress, and rumination were significantly positively correlated (r = 0.324–0.484, p < 0.001). Cognitive avoidance significantly predicted rumination (t = 0.347, p < 0.001). Further, three indirect paths were identified: the mediating effect of perfectionism, the mediating effect of stress, and a chain mediating effect through both (95% CIs excluded zero). These findings suggest that cognitive avoidance influences rumination directly and indirectly through perfectionism and stress, offering insights into maladaptive cognitive-emotional patterns in college students.